Changes of hematological indices in patients with diffuse toxic goiter - F. H. Saidova; L. M. Ahmedova; Zh. B. Aslanova; N. A. Najafov (Клінічна хірургія, 2021)
Objective. To reveal the incidence of various morphological types and degrees of the anemia severity in patients with diffuse toxic goiter.